The Effects of Online Collaborative Writing via Google Docs on Learners’ Writing Performance and Interaction: A Case Study of Asian EFL Learners - Kitjaroonchai, Nakhon; Suppasetseree, Suksan (8ISC Abstract Proceedings, 2022)
This study investigated the effects of online collaborative writing and writing contributions in Google Docs of 35 Asian EFL university learners in a composition course. Data were collected from students’ pre-test and post-test writing, two extended online collaborative tasks: writing descriptive and argumentative essays, and student reflections. Students’ writing performances were assessed using Jacob et al.’s (1981) composition analytic scoring rubric. Paired sample t-test analysis showed that academic writing performance significantly increased after participating in two extended online collaborative writing tasks. Learners’ writing performance has improved substantially, as observed in the increase of mean scores for each language domain, including content, organization, vocabulary, language use, and mechanics. The findings revealed that learners developed more extended written texts, and texts were more accurate in the post-test writing. Furthermore, the Pearson correlation coefficient (Pearson’s r) analysis showed that learners’ text contributions, their use of writing change functions, and language functions during the collaborative process were positively correlated with their post-writing performance. This study supports the notion of writing as an exploratory and recursive process but not linear. Implications of the study were also discussed. Keywords : online collaborative writing, EFL learners, performance, interaction